Circular RNAs: New Epigenetic Signatures in Viral Infections - Nahand, Javid Sadri; Jamshidi, Sogol; Hamblin, Michael R.; Mahjoubin-Tehran, Maryam; Vosough, Massoud; Jamali, Marzieh; Khatami, Alireza; Moghoofei, Mohsen; Baghi, Hossein Bannazadeh; Mirzaei, Hamed (Frontiers in Microbiology, 2020)
Covalent closed circular RNAs (circRNAs) can act as a bridge between non-coding RNAs and coding messenger RNAs. CircRNAs are generated by a back-splicing mechanism during post-transcriptional processing and are abundantly expressed in eukaryotic cells. CircRNAs can act via the modulation of RNA transcription and protein production, and by the sponging of microRNAs (miRNAs). CircRNAs are now thought to be involved in many different biological and pathological processes. Some studies have suggested that the expression of host circRNAs is dysregulated in several types of virus-infected cells, compared to control cells. It is highly likely that viruses can use these molecules for their own purposes. In addition, some viral genes are able to produce viral circRNAs (VcircRNA) by a back-splicing mechanism. However, the viral genes that encode VcircRNAs, and their functions, are poorly studied. In this review, we highlight some new findings about the interaction of host circRNAs and viral infection. Moreover, the potential of VcircRNAs derived from the virus itself, to act as biomarkers and therapeutic targets is summarized.